Flexible next‐generation robotic surgical system for transoral endoscopic hypopharyngectomy: A comparative preclinical study. Issue 1 (11th November 2017) - Tateya, Ichiro; Koh, Yoon Woo; Tsang, Raymond K.; Hong, Steven S.; Uozumi, Ryuji; Kishimoto, Yo; Sugimoto, Taro; Holsinger, F. Christopher
Abstract: Background: The purpose of this cadaveric study was to determine the efficacy of a flexible, next‐generation robotic surgical system for transoral robotic hypopharyngectomy. Methods: A comparative evaluation study of the flexible versus rigid robotic surgical systems for the hypopharynx was conducted using 3 cadavers. Endpoints for assessment were visualization of the hypopharynx, access to the hypopharynx, and difficulty of dissection. Hypopharyngectomy was performed on 3 other cadavers using the da Vinci Sp surgical system. Results: Access to the apex of the pyriform sinus and the esophageal inlet was easier with the da Vinci Sp than with the da Vinci Si. Dissection with the da Vinci Sp was easier in all areas of the hypopharynx than with the da Vinci Si. Robotic hypopharyngectomy was successfully completed on all cadavers using the da Vinci Sp surgical system. Conclusion: Preclinical testing in human cadavers suggests that flexible robotic surgery may facilitate successful transoral hypopharyngectomy.